Visualização de dados na internet - Ribeiro, Daniel Melo (2009)
This study discusses the new challenges compelled by information technologies from the following question: how to deal with the excess of information. The search for ways to promote knowledge in cyberspace demands investigations of more intelligent representations. We face the need to reorganize the information in the digital space, which in turn requires a deeper look on the practices of design. Deepen the role for the designer as a creator of interfaces of cyberspace, this study recovers the important contribution made by the information design, field of study that investigates the understanding of information through visual representations. Considering cartography as a human need to achieve visual representations of complex systems of information, the visualization, in the context of this research, is regarded as a fundamental instrument to reveal hidden meanings, invisible in a observation restricted to data itself. Manovich links the concept of mapping to visualization. Since all digital data is represented with the same digital code, computers can easily map one representation to another. Then, visualization can be conceived as a kind of mapping, in which data is mapped to image. The main objective here is to investigate data visualization applications that meet the challenges imposed by the excess of information. To discuss the hypothesis that the data visualization is relevant to generate knowledge, this work examines models of interactive visualization of dynamic data from a sample of applications available on the Internet. With this overview of the types of visualization, a classification was created based on the need to understand the context and the symbolic relations of individuals on the Internet. Finally, some future directions of studying information, design and visualization are pointed out